A 5-year examination of CAPABLE implementation using RE-AIM and CFIR frameworks - Paone, Deborah L.; Schuller, Jeanne W.; Smith, Matthew Lee; Gitlin, Laura N.; Szanton, Sarah L. (Frontiers in Public Health, 2025)
BackgroundExamining the experience of organizations implementing evidence-based programs can help future programs address barriers to effective implementation, sustainment, and scaling. CAPABLE is an evidence-based 4-to-6-month program that improves daily function of older adults and modifies their home environments in modest ways to support their goal attainment. Through a guided process, utilizing an occupational therapist, nurse, and handy worker, the older adult sets goals and a personal action plan. In this study, we examined factors that advanced or impeded implementation and sustainability of CAPABLE. The researchers are embedded in the CAPABLE National Center and Johns Hopkins and provide ongoing technical support in implementation and dissemination of CAPABLE throughout the U.S., Canada, and other countries.MethodsWe chose the RE-AIM and CFIR frameworks based on their robust use in the U.S. for examining implementation of older adult health promotion and prevention programs. We examined the implementation and sustainment experience of 65 organizations adopting CAPABLE across 5 years (2019–2024). Data sources included licensure records, an annual survey, and additional notes collected ad hoc. We identified key components to implement CAPABLE and used self-reported data from the lead program administrator at each organization who replied to the annual survey. These key informants responded to the level of ease or difficulty of these key components required for implementation. They responded each year that their organizations provided CAPABLE. CAPABLE licensure records indicated when the organization began/terminated their service. Notes from monthly office hours calls provided additional contextual information. We performed qualitative thematic and descriptive analysis on the notes. We also reviewed published studies on CAPABLE’s outcomes. The unit of analysis was the organization.ResultsThe following factors were consistently reported by these administrators as supporting ease of implementation: getting leadership support, accessing technical assistance, and maintaining fidelity to the program. Conversely, common challenges reported included difficulty with recruitment, hiring/finding the required personnel, and sustainability funding. Internal factors supporting readiness and adoption were perceived value of the program and program manager knowledge and commitment. External factors reported that supported adoption was initial funding to start a pilot, and alignment with “aging in community” strategic goals.ImplicationThis examination revealed positive and impeding forces for implementation and sustainment and identified where additional support was needed. Findings are guiding the development of this additional technical support by the CAPABLE National Center. In addition, efforts are underway to improve funding and policy to support CAPABLE to improve sustainment, scaling, and dissemination. This study also provides a use case for employing the RE-AIM and CFIR frameworks together to track ongoing implementation. This helps address a gap in the literature concerning practical ways to monitor, evaluate, and report on ongoing implementation of evidence-based programs.